Pengembangan Aplikasi Catering Pada Rumah Makan Berbasis Mobile - Jihad; Fachrie, Muhammad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Ordering catering is an activity carried out by customers to buy products in the form of food. At the Tebar Rasa Restaurant, the catering ordering process is carried out by customers by coming directly to the location. Based on the author's interviews with related parties, in the process of ordering catering there are several customers who complain about the ordering process because it takes more time, effort and costs. As a solution to this problem the authors built a Web and Mobile-Based Catering Order Application to assist in the process of ordering catering by customers. In making this application the author uses the android programming base and MySQL as the data storage. This application is made to streamline time, effort and produce accurate information. The results of testing the built application have performance according to user needs. By combining the advantages of the PHP and Java programming languages, this research has the potential to create a more efficient and satisfying food ordering experience for customers.